The college premium rollercoaster and the rebound of lifetime wage growth: A structural analysis - Raquel Fonseca; Etienne Lalé; François Langot; Thepthida Sopraseuth (Université du Québec à Montréal, École des sciences de la gestion (ESG UQAM), Département des sciences économiques, 2025)
We develop a general-equilibrium OLG model of human capital to study the dynamics of the U.S. college premium and lifetime wage profiles between 1940 and 2020. The model features endogenous education and on-the-job training, along with exogenous aggregate (skill-neutral and skill-biased) shocks and cohort-specific trends in initial human capital endowments and learning capabilities. The estimated model replicates the W-shaped evolution of the college premium and the flattening then steepening of lifetime wage profiles. We show that changes in labor efficiency, rather than changes in relative skill prices, are the main driver of these dynamics. We quantify the contribution of estimated exogenous drivers and find a key role for the deterioration of human capital endowments and learning abilities among more recent cohorts. Crucially, endogenous adjustments in educational attainment and skill prices serve as powerful equalizing forces. Without these market mechanisms, the gap between the lifetime wage profiles of skilled and unskilled workers would widen and the college premium double.
Keywords: E24; E25; J24; J31; 330; College premium; Life-cycle wage profile; On-the-job training; Human capital; Technological progress